Analisis Musikologis Struktur Lagu Gerobak Buruk Sapi Gile Kesenian Gitar Tunggal Sungai Pinang Kabupaten Ogan Ilir - Silo Siswanto; Irfan Kurniawan (FBS Universitas Negeri Padang, 2021)
This study discusses the musical phenomenon of the reportoar song Gerobak Buruk Sapi Gile which is a characteristic of guitar tunggal art musicals in Sungai Pinang sub-district, Ogan Ilir district. The purpose of this research is to find out and understand more deeply the concepts of the single guitar musical culture. The approaches taken are; musicological analysis. This study uses qualitative methods with data collection techniques through observation, interviews and documentation. The results of interviews and documentation of guitar tunggal music were analyzed through laboratory work using the analytical transcription method. The results of this study describe the form and structure of the song of the bad cow gile cart which consists of; scale system analysis, cadence melody analysis, antisedent and consequent phrase analysis, song period analysis, and bar analysis.